2022
DOI: 10.1029/2021ea002168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Learning Rates and Optimization Algorithms on Forecasting Accuracy of Hourly Typhoon Rainfall: Experiments With Convolutional Neural Network

Abstract: Accurate typhoon rainfall forecasting has become a great concern among the scientific community because typhoons' heavy rainfall results in coastal flooding that leads to loss of lives and properties. Typhoon In-Fa, a recent typhoon in China, for example, affected millions of people in Henan province by its heavy rainfall and floods (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…A seasonal pattern means a repeated pattern in the time series, and the forecasting model can be affected by seasonality, as confirmed by the earlier study (Kwiatkowski et al, 1992). Recent studies (e.g., Prabhakaran, 2019;Uddin et al, 2022a) confirmed that when a time series had no seasonal effect, the outputs were more reliable. More information about the additive decomposition method is available in Seabold and Perktold (2010) (https://www.statsmodels.org/stable/index.html).…”
Section: Model Constructionsupporting
confidence: 52%
See 1 more Smart Citation
“…A seasonal pattern means a repeated pattern in the time series, and the forecasting model can be affected by seasonality, as confirmed by the earlier study (Kwiatkowski et al, 1992). Recent studies (e.g., Prabhakaran, 2019;Uddin et al, 2022a) confirmed that when a time series had no seasonal effect, the outputs were more reliable. More information about the additive decomposition method is available in Seabold and Perktold (2010) (https://www.statsmodels.org/stable/index.html).…”
Section: Model Constructionsupporting
confidence: 52%
“…used the first 30 years (360 months) for training the model and the last 8 years (96 months) for evaluating the forecasting performance of the SVM, RF, CNN, and LSTM models. A grid search with the k-fold cross-validation method was employed in this study to find out the best parameters for the SVM, RF, CNN, and LSTM models, as proposed byUddin et al (2022aUddin et al ( , 2022b. The whole training dataset was cross-validated by using this method.…”
mentioning
confidence: 99%
“…Future work could assess whether use of predictors that describe the spatial patterns of meteorological conditions, or use of other machine learning architectures such as convolutional neural networks (Uddin et al., 2022), can improve wind gust forecasting. It may also be useful to examine whether use of predictors from other reanalyzes or higher resolution datasets enhances forecast skill.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examine the formulations of SGD, Adam, RMSprop, AdaGrad, AdaDelta, and Nadam [17].…”
Section: The Optimizer Used In the Efficientnet Architecturementioning
confidence: 99%